Poster Typographic days 8 - Panayides, Angelos (My University, 2025)
The Lahti International Poster Triennial celebrates its 50th anniversary! Finland hosts 22nd international poster exhibition. June 6–September 7, 2025, Lahti Museum of Visual Arts Malva Opening ceremony June 5, 2025 The Lahti International Poster Triennial will celebrate its 50th anniversary in 2025. Continuing a tradition that began in 1975, this graphic design competition and exhibition will now be held for the 22nd time in Lahti. To honour the triennial’s 50th jubilee, the theme of our special anniversary category will be ‘freedom of expression’. Although this inherent human right is protected in many countries, free speech still remains under threat in many parts of the world. The triennial is a collaboration between: Lahti Museum of Visual Arts Malva Grafia, Association of Visual Communication Designers in Finland The Finnish Friends of Posters Guild Amnesty International Finnish Section Lauri Tarasti Organising committee Marion Robinson, Graphic Designer, Chair of the Lahti Poster Triennial Hanna Suihko, Collections Curator, Malva, Secretary General of the Poster Triennial, Chair of the Organizing Committee Pekka Loiri, Graphic Designer, Advisory Member Esa Ojala, Graphic Designer, Professor, Advisory Member Pekka Piippo, Graphic Designer Katri Soramäki, Executive Director, Grafia Klaus Welp, Graphic Designer
Cultural, social and ideological posters
Keywords: Triennial, Poster, Graphic Design, Exhibition